Unlocking winter maize potential: pioneering on-farm strategies for resilient yields in challenging climates - Jat, Raj Kumar; Durgude, Shubham; Meena, Vijay Singh; Sohane, RK; Singh, RN; Reddy, Illathur R.; Kumar, Suneel; Pazhanismy, S.; Meena, Sunita Kumari; Sharda, Kumari; Singh, Susheel; Singh, Rama Kant; et al. (Frontiers in Agronomy, 2025)
What are the key factors influencing yield in winter maize cultivation under adverse climatic conditions? How can on-farm experimentation reveal innovative strategies to improve production in these challenging environments? Four year (2020-21-to-2023-24) on farm experimentation at 160 farmers in the districts of Purnia and Katihar were consider for study. The key factors evaluated for maize yields encompassed sowing windows, varietal performance, topography, seed treatment, earthing up, planting methods, spacing, tillage practices, irrigation, and nutrient management. Data was collected using a structured questionnaire that was validated by visiting on-farm experimentation at fields. Results indicated that the optimal sowing window for high yields was October 25th to November 7th, with high-yielding varieties Grover 4455 and Srikar 1818 showing the best performance. Topography showed a preferential distribution of yield towards upland areas. The variety P3355 demonstrated consistent performance, appearing across both high and medium yield categories. Higher frequencies of high yields in seed-treated plots were nevertheless obtained, with 62% high yields obtained in treated plots against 48% obtained in plots without treatment. At earthing up is one of the critical practices in flat bed system (FBS), and it contributed much to higher yields (χ²=17.86, p=0.003), but in raised bed system (RBS), which allow superior yields intrinsically. This trial showed that optimum spacing of 50 cm row-to-row and 22 cm plant-to-plant, coupled with moderate tillage operations of 4-10, with a median of 6, resulted in increased yields. Efficient irrigation management, where high-yielding plots received balanced nutrient applications of 243.85-165.51-106.74 NPK kg/ha, was a critical factor in realizing high yields. Principal component analysis (PCA) underlined the role of integrated agronomic practices in maximizing maize production. It provides actionable insight to farmers with respect to maize yield improvement for economic resilience and sustainable agriculture. Overall, this study identified optimal sowing windows, high-yielding varieties, and integrated agronomic practices that significantly enhance winter-maize production under adverse climatic conditions, offering actionable insights for sustainable agriculture.